The Ultimate Reality in the Universe: A Study on the Views of Quantum Physics and Vedanta Philosophy - Gain, Jatindranath (Studies in Philosophy of Science and Education, 2023)
The majority of quantum mechanics' founding fathers were sensitive to the philosophical implications of quantum mechanics. The theories of relativity developed by Einstein also turned out to have philosophical implications. Although quantum physics could seem enigmatic, it explains everything in our environment, whether we are aware of it or not. Using the abilities of quantum physics results in the expansion of innovative technologies, both for use now and maybe in the future. Everything is explained by quantum physics, which provides the greatest description we currently have of the nature of the particles in the cosmos. The efforts to explain the universe in terms of quantum physics, which regulates the behaviour of the subatomic, microscopic world, are presented in Quantum Universe. It shows a revolution in quantum physics as well as a quantum leap in our understanding of the universe's mystery and beauty. Quantum physics is trying to find a common singularity for all objects. They are trying to discover the ‘Theory of Everything, that will explain everything in this universe. Vedanta and Quantum Physics both are looking for the same underlying reality and searching for the absolute truth in the universe, though their approach to searching is different. This paper will attempt to concentrate on the perspectives of Quantum Physics & Advaita Vedanta about the ultimate reality in the universe, the nature of consciousness.